Ikaros family zinc finger 1 regulates dendritic cell development and function in humans - Urszula Cytlak (Nature Portfolio, 2018)
IKZF1 is a transcription factor known to regulate mammalian B-cell development. Here the authors show that IKZF1 is required for human pDC development and regulation of DC cytokine production in patients with IKZF1 haploinsufficiency, findings which are recapitulated in lenalidomide-induced IKZF1 deficiency.